THE INFORMATION SYSTEM AND SPEECH ACTS PROCESS OF TORAJANESE-MAMASAN COMMUNITY IN THE MARRIAGE PROPOSAL IN KOLAKA DISTRICT - Z. Zakaria (Journal of English Education, 2017)
Marriage proposal process of Torajanese-Mamasan is a kind of culture product in social custom and brought some communication acts, such as speech acts, norms, and social custom values upon it. The scope of the research focused on the manner of meaning semantically, pragmatically, and ethics that formed in communication custom system in the process of marriage proposal, instead that the research need to explain all the process of marriage proposal step by step orderly. The researcher used Ethnomethodology approach, and also used two kinds of source of the data,; primary and secondary data and analyzed them in qualitative. The result showed that the process started from ma’bisik, mangusik, ma’pasule kada until ma’randang process were run by social custom system in communities of Torajanese-Mamasan in Kolaka district. And also, that the all of process were planned and done by adult named to matua verbally and symbolically. There was interesting thing of the process, that the communication system to be done associatively, bear several art and ethic values.